The Influence of Inflation, Exchange Rate, BI Rate, and Federal Funds Rate on the Indonesia Composite Index during the Global Monetary Policy Tightening Era 2022–2025 - Tri Yuliana; Edi Wibowo (The Indonesian Institute of Science and Technology Research, 2026)
The era of global monetary policy tightening between 2022 and 2025 has introduced significant uncertainty into the Indonesian capital market, creating an urgent need to identify which macroeconomic factors most effectively dictate stock price movements. This research investigates the influence of Inflation, the Rupiah Exchange Rate, the BI Rate, and the Federal Funds Rate on the Indonesia Composite Index. Using a quantitative descriptive method, this study analyzed 48 monthly secondary data observations. The statistical analysis was performed using SPSS 26 for Windows, employing Multiple Linear Regression Analysis as the primary method. To ensure the reliability of the model, the researchers conducted a series of Classical Assumption Tests, including Kolmogorov-Smirnov for normality, VIF for multicollinearity, the Runs Test for autocorrelation, and the Rank Spearman method for heteroskedasticity. The results of the partial significance test (t-test) demonstrate that only the Rupiah Exchange Rate has a significant effect on the IHSG, while Inflation, the BI Rate, and the Federal Funds Rate show no significant impact. The F-test confirms the model's accuracy, with an Adjusted R2 of 0.153. In conclusion, the findings suggest that in a high-interest-rate environment, the volatility of the national currency is the most critical signal for the market, whereas other macroeconomic shifts were largely anticipated and absorbed by investors.